Um controlador adaptativo robusto aplicado a conversores estáticos conectados à rede elétrica através de filtro LCL - Tambara, Rodrigo Varella (2014)
This Thesis deals with the development of a novel robust model reference adaptive controller (RMRAC), in discrete-time applied to grid-connected systems using LCL filter. This controller uses a modified robust parameters identifier based on a recursive least-squares algorithm. Two control structures are analyzed: state feedback approach and input-output approach. The robust stability analysis of the controller is presented including unmodeled dynamics. Thus, through these analyses, constraints design, in discrete-time, are obtained. For the validation of the proposed control algorithm, simulation and experimental results of a grid-connected power converter with LCL-filter, with current control, are presented.